2021
DOI: 10.1051/0004-6361/202039764
|View full text |Cite
|
Sign up to set email alerts
|

Semianalytical model for planetary resonances

Abstract: Context. Planetary resonances are a common dynamical mechanism acting on planetary systems. However, no general model for describing their properties exists, particularly for commensurabilities of any order and arbitrary eccentricity and inclination values. Aims. We present a semianalytical model that describes the resonance strength, width, location and stability of fixed points, and periods of small-amplitude librations. The model is valid for any two gravitationally interacting massive bodies, and is thus a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…a p ∼ 0.35 AU). Radius, period, and coplanarity values are affected by observational biases (Martin E-mail: egianuzzi@mi.unc.edu There is some evidence that the N/1 mean motion resonances (MMRs) are related to the planetary parking location and their evolution in the disc, as they lead to strong regions of chaos around the binaries (Gallardo et al 2021). For example, Zoppetti et al (2018) applied a simplified model to Kepler-38 and suggested a capture in 5/1 MMR with subsequent tidal evolution of the planet outside MMRs.…”
Section: Introductionmentioning
confidence: 99%
“…a p ∼ 0.35 AU). Radius, period, and coplanarity values are affected by observational biases (Martin E-mail: egianuzzi@mi.unc.edu There is some evidence that the N/1 mean motion resonances (MMRs) are related to the planetary parking location and their evolution in the disc, as they lead to strong regions of chaos around the binaries (Gallardo et al 2021). For example, Zoppetti et al (2018) applied a simplified model to Kepler-38 and suggested a capture in 5/1 MMR with subsequent tidal evolution of the planet outside MMRs.…”
Section: Introductionmentioning
confidence: 99%
“…Lithwick & Wu 2008a;Cheng et al 2014b;Woo & Lee 2018;Kenyon & Bromley 2021), which are considered to be strongest around binaries (e.g. Cuello & Giuppone 2019;Gallardo et al 2021). However, Lithwick & Wu (2008b) found some difficulties in adjusting the values of Charon's eccentricity, e C : in order to safely transport Nix to the 4/1 MMR, it should be e C < 0.024, while in order to transport Hydra to the 6/1 MMR, it should be e C > 0.04.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that the N/1 mean motion resonances (MMRs) are related to the planetary parking location and their evolution in the disc, as they lead to strong regions of chaos around the binaries (Gallardo et al 2021). For example, Zoppetti et al (2018) applied a simplified model to Kepler-38 and suggested a capture in 5/1 MMR with subsequent tidal evolution of the planet outside MMRs.…”
Section: Introductionmentioning
confidence: 99%